Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5ra05254h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physical properties of tris(dialkylamino)cyclopropenium bistriflamide ionic liquids

Abstract: An investigation of symmetry (D3h, C3h, C2v and Cs) and alkyl chain length (6–60 alkyl carbon atoms) effects on the physical properties of peralkylated triaminocyclopropenium bistriflamide salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 76 publications
(32 reference statements)
0
45
0
Order By: Relevance
“…DT1 was successfully synthesized and characterized by 1 H NMR, 13 C NMR, and high resolution mass spectrometry (HRMS) and its purity was confirmed by liquid chromatography‐mass spectrometry (LCMS). However, DMSO and chloroform solutions of DT1 decompose within few hours to give complex mixtures of ring‐opened products (Figure S1) …”
Section: Resultsmentioning
confidence: 99%
“…DT1 was successfully synthesized and characterized by 1 H NMR, 13 C NMR, and high resolution mass spectrometry (HRMS) and its purity was confirmed by liquid chromatography‐mass spectrometry (LCMS). However, DMSO and chloroform solutions of DT1 decompose within few hours to give complex mixtures of ring‐opened products (Figure S1) …”
Section: Resultsmentioning
confidence: 99%
“…[28] Hysteresis and passivation were observed for cases 1 and 2 at the GC electrode, consistent with the electrochemistry of the cation rather than the [Tf 2 N] À anion;o xidation was also more facile at the platinum electrode. Although multiple authors have reported anionsl imitingt he reductive electrochemical window of ionicl iquids, [32] the resultsd escribed here are only the second example after that of the cyclopropenium salts reported by Curnow et al [33] of an ionic liquid cation limiting the oxidative window of an ionic liquid.…”
Section: Electrochemical Windows Of Ionic Liquids1-3 and 10mentioning
confidence: 57%
“…CH 2 Cl 2 , CHCl 3 , diethylether, ethanol, petroleum ether, D 2 O, tributylamine, dibutylamine and bis(2,2,2‐trifluoroethyl)amine were obtained commercially. [C 3 (NMe 2 ) 3 ]Cl was prepared by a literature method . Solvents were dried using an in‐house solvent purification system.…”
Section: Methodsmentioning
confidence: 99%